Uracil/tegafur as a possible salvage therapy in chemo-refractory colorectal cancer patients: a single institutional retrospective study - Bayoglu, İbrahim V.; Yildiz, Ibrahim; Varol, Umut; Cokmert, Suna; AlacacIoğlu, Ahmet; Kucukzeybek, Yuksel; Akyol, Murat; Demir, Lutfiye; Dirican, Ahmet; Tarhan, Oktay (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Our aim was to determine the activity and toxicity of uracil/tegafur and leucovorin combination in metastatic colorectal cancer (mCRC) patients who have progressed with all currently active agents. Material and methods : This study was a retrospective analysis of 50 mCRC patients who had previously failed to respond to all available chemotherapeutics and who received subsequent treatment with uracil/tegafur 250 mg/md1–5 in combination with leucovorin 90 mg/day, d1–5 followed by two days’ rest. Results: The median age of the patients was 60 years. Most of them (60%) were male. Bevacizumab was used in 65% and cetuximab in 55% of the patients. Thirty-nine patients (78%) were treated with uracil/tegafur in the fourth line setting. The median treatment duration was 4.2 months (range, 2–24 months). The objective response rate and the disease control rate were 4% and 34%, respectively. Median progression-free survival was 4.1 months (95% CI, 3.6–4.6 months) and overall survival was 6.6 months (95% CI, 4.5–8.6 months). Grade 3 or 4 toxicity was seen in 20% (n = 10) of the patients while 60% (n = 6) of them required dose reductions. Conclusions : This retrospective data show that uracil/tegafur may be considered in heavily pretreated mCRC patients because of its activity, lower toxicity, and feasibility.